Ethnomathematics exploration in the Galasin traditional games in Jakarta on mathematical concepts - Ayu Setyawati; Jiddan Fakhri Sunni; Joko Soebagyo (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to explore ethnomathematics in the traditional game Galasin in Jakarta on mathematical concepts such as gradients, point to point distance, and vectors. This study uses an ethnographic approach to obtain a description of an in-depth analysis of a culture based on the information that has been obtained and by conducting observations and interviews in data collection. This research focuses on one of the traditional games in Jakarta, namely the Galasin game as a form of understanding ethnomathematics in mathematical concepts such as vectors, gradients, and point to point distances. This shows that the traditional game Galasin in Jakarta has a connection with mathematical concepts and forms of deepening in previous studies which have links with geometric mathematical concepts such as flat shapes. The existence of traditional game media in learning mathematics can provide benefits, namely visualizing mathematics learning in a real form so that students become more understanding and easier to understand learning the mathematical concepts being studied.